Here is the initial term and recursive formula for a sequence:

[tex]\[
\begin{array}{l}
f(1) = 40 \\
f(n) = -f(n-1)
\end{array}
\][/tex]

Which explicit formula can be used to define this sequence?

[tex]\[
\begin{array}{cc}
A. \, f(n) = -39^{n-1} & C. \, f(n) = 39 \\
B. \, f(n) = 40 & D. \, f(n) = 40(-1)^{n-1}
\end{array}
\][/tex]



Answer :

Let's determine the explicit formula for the given sequence step-by-step.

The sequence is initially defined as follows:
[tex]\[ f(1) = 40 \][/tex]
[tex]\[ f(n) = -f(n - 1) \][/tex]

To understand the pattern in the sequence, let's evaluate the first few terms:

1. For [tex]\( n = 1 \)[/tex]:
[tex]\[ f(1) = 40 \][/tex]

2. For [tex]\( n = 2 \)[/tex]:
[tex]\[ f(2) = -f(1) = -40 \][/tex]

3. For [tex]\( n = 3 \)[/tex]:
[tex]\[ f(3) = -f(2) = -(-40) = 40 \][/tex]

4. For [tex]\( n = 4 \)[/tex]:
[tex]\[ f(4) = -f(3) = -40 \][/tex]

5. For [tex]\( n = 5 \)[/tex]:
[tex]\[ f(5) = -f(4) = -(-40) = 40 \][/tex]

From these calculations, it's clear that the sequence alternates between [tex]\( 40 \)[/tex] and [tex]\( -40 \)[/tex].

Let's identify the pattern:

- When [tex]\( n \)[/tex] is odd (1, 3, 5,...), [tex]\( f(n) \)[/tex] is [tex]\( 40 \)[/tex].
- When [tex]\( n \)[/tex] is even (2, 4, 6,...), [tex]\( f(n) \)[/tex] is [tex]\( -40 \)[/tex].

This alternating sign can be expressed using the term [tex]\((-1)^{n - 1}\)[/tex]:

- For [tex]\( n = 1 \)[/tex], [tex]\( (-1)^{1-1} = (-1)^0 = 1 \)[/tex]
- For [tex]\( n = 2 \)[/tex], [tex]\( (-1)^{2-1} = (-1)^1 = -1 \)[/tex]
- For [tex]\( n = 3 \)[/tex], [tex]\( (-1)^{3-1} = (-1)^2 = 1 \)[/tex]
- For [tex]\( n = 4 \)[/tex], [tex]\( (-1)^{4-1} = (-1)^3 = -1 \)[/tex]

Hence, the explicit formula is:
[tex]\[ f(n) = 40 \cdot (-1)^{n - 1} \][/tex]

Among the given options, the correct explicit formula that matches our derivation is:
[tex]\[ f(n) = 40 \cdot (-1)^{n - 1} \][/tex]

Thus, the explicit formula used to define this sequence is:
[tex]\[ f(n) = 40 \cdot (-1)^{n - 1} \][/tex]